HASIL BELAJAR DAN MOTIVASI SISWA DENGAN PENGGUNAAN BOOKLET PADA MATERI SISTEM PERTAHANAN TUBUH - Fatimah, Siti; Jayanti, Sri; Fitria, Dini (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2025)
Education is one of the most important components in the success of a country. The implementation of the learning process is still a challenge for many educational units. Pocket books are one of the learning resources used to support learning. This study uses a pocket book containing information about the body's defense system to assess the learning outcomes and motivation of class XI students of SMA Negeri 1 Secanggang. The True Experimental Design method is applied in this quantitative research design. A total of 62 students from class XI IPA 5 of SMA Negeri 1 Secanggang (experimental class) and XI IPA 3 (control class) became the research sample. Analysis of t-test data. The results of this study indicate that the influence of the Body's Defense System booklet has a significant impact on the learning outcomes of students of SMA Negeri 1 Secanggang. The results of the t-test show that Ha is accepted and Ho is rejected, namely t count> t table 8.96> 2.000 with a significance level of Î± = 0.05 and t count> t table 8.96> 2.660 with a significance level of Î± = 0.01. Furthermore, the results of this study indicate that the learning motivation of students of SMA Negeri 1 Secanggang is significantly influenced by the Body Defense System booklet. The results of the hypothesis test tcount> ttable 11.69> 2.000 with a significance level supporting this. Keywords: Booklet, Learning Outcomes, Motivation